Virtual patient simulation: Promotion of clinical reasoning abilities of medical students - Rokhsareh Aghili; Mohammad E. Khamseh; Mansoureh Taghavinia; Mojtaba Malek; Zahra Emami; Hamid R. Baradaran; Mahboobeh Khabaz Mafinejad (Knowledge Management & E-Learning: An International Journal, 2012)
Objectives: Virtual patient simulation (VPS) is used in the education of health care professionals. This method brings an opportunity for the learner to examine necessary diagnostic and therapeutic skills. The aim of this study was to assess the efficacy of VPS on clinical reasoning abilities of medical students and to evaluate their attitude towards VPS in clinical endocrinology course in a teacher centered educational environment.Methods: Fifty-one medical students in their 6th academic year were simply randomized in two groups, the simulation and the control. The students in the simulation group were provided by an application which presented them virtual case scenarios on diagnosis and management of thyroid nodules and osteomalacia. All the students sat for a diagnostic test at the beginning and at the end of the course. The test comprised a series of essay questions matched for their academic level and closely related to the case scenarios. They were also asked to complete a questionnaire to assess their attitude towards the application.Results: Participants in both groups did not have any statistical differences in scientific background in basic sciences (P=0.672) and prior clinical examinations (P=0.376). At completion of the course the mean score of the students in the simulation group improved significantly compared to the students in the control group by 3.5 vs. 1.0 points (P=0.001). The students found the application worthful and showed a positive attitude towards it.Conclusions: Virtual patient simulation improved clinical reasoning abilities of medical students in the context of a traditional teaching/learning environment.